Clinic based hearing screening protocols : the feasibility of implementing the Health Professions Council of South Africa Year 2007 Guidelines. - Petrocchi-Bartal, Luisa (My University, 2011)
Purpose: This study aimed to assess the feasibility of implementation of the Health Professions Council of South Africa's (HPCSA) clinic-based hearing screening subsection of its 2007 Position Statement on Early Hearing Detection and Intervention (EHDI) programmes in South Africa. Specific sub-aims included (a) establishing the prevalence of hearing screening conducted at Maternal Child Woman’s Health (MCWH) immunisation clinics; (b) determining the hearing screening procedures and protocols in use at MCWH immunisation clinics; (c) determining and exploring the possible concomitant personnel-associated factors which may influence the implementation of newborn and infant hearing screening programmes; (d) determining and exploring other factors that may have influenced implementation of newborn and infant hearing screening; and lastly, (e) comparing any hearing screening procedures and protocols in use to the HPCSA (2007) EHDI position statement clinic guidelines and associated clinic benchmarks Participants: Thirty primary healthcare immunisation clinic managers/acting managers were interviewed in two South African sample groups, in the North West province (NW) and Gauteng (GP). Design: An exploratory, non-experimental, qualitative research design was employed incorporating both quantitative and qualitative information within the two sample groups. Methods and Materials: An interview using a questionnaire was administered with primary health care (PHC) clinic nursing manager/acting manager, placed within the identified sites. The questionnaire encompassed areas such as work contexts, hearing screening contexts and information management systems, as well as quality control measures in place at these clinics. Data Analysis: Content analysis was used to code emergent themes into specific categories. Frequency calculations of the emergent themes were calculated and results described qualitatively. Results: No PHC clinics placed within the identified sites offered or provided formalised newborn/infant hearing screening and none of these facilities had equipment to do so. Most sites attributed the lack of formalised hearing screening to budgetary and human resource issues, staff training in particular. Non-formalised hearing screening protocols in place demonstrated inconsistencies in application across districts and none complied with HPCSA (2007) clinic guidelines. Most respondents were willing to implement formalised hearing screening to coincide with their immunisation schedules. The immunisation context was considered favourable for implementation of formalised hearing screening. Other factors such as reduced parental awareness of the importance of hearing screening, and caregiver cultural issues were considered surmountable by respondents. Conclusions: HPCSA (2007) implementation of clinic hearing screening protocols at PHC immunization clinics (level one) does not appear to be feasible based on current evidence. Results from the current study have assisted in identifying procedural and logistical assets and barriers to implementation of HPCSA (2007) clinic guidelines for EHDI at immunisation clinics in South Africa. Future research implications include formal investigations of central directorate versus district differences in PHC Package Integrated Management of Childhood Illnesses (IMCI); Otitis Media, and Road to Health Chart (RtHC) protocols; provincial and district inequities in funding as they impinge on hearing health care service delivery; costing of rudimentary protocols in place versus formalised HPCSA (2007) EHDI service delivery; research into parental awareness, education and willingness in specific reference to certain procedures such as otoacoustic emissions; and replication of the current study throughout the country for quantitave data with increased ability to draw causal inferences and generalize findings.
Keywords: Health Professions Council of South Africa; Early hearing detection and intervention; Primary healthcare immunisation clinics; Interview